Changes in Liver and Kidney Malondialdehide Levels of Diabetic Rats that Given Diet of Caulerpa racemosa Seaweed - Yusasrini, N. L. A; Mayun Permana, I. D. G (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 8 No 1 (2021): Scientific Journal of Food Technology (March), 2022)
Caulerpa racemosa seaweed is a type of seaweed that can be used as an antidiabetic. Previous studies have shown that Caulerpa. sp. was able to reduce blood glucose levels and showed the regeneration of pancreatic ? cells in diabetic rats. The purpose of this study was to determine the effect of C. racemosa seaweed diet on liver and kidney malondialdehyde levels in diabetic rats. The research stages began with chemical analysis of C. rasemosa seaweed flour and continued with bioassay testing. The analysis included proximate analysis, fiber, total phenol and antioxidant activity of C. rasemosa seaweed, analysis of blood sugar in serum and malondialdehyde (MDA) in the liver and kidneys. Results showed that C. rasemosa seaweed flour contained 11.37% water, 23.24% of ash content, 12.84% of protein, 2.02% of fat, 50.45% of carbohydrate by different, 6.35% of crude fiber, total phenol 2785 mg GAE / g, and 15.68% of antioxidant activity. Diet of C. rasemosa seaweed flour for 30 days was able to reduce blood glucose levels by 53.12% in the diabetic rat group. Liver MDA levels in the group of diabetic rats fed a diet C. rasemosa decreased 17.79% compared to the control group. Renal MDA levels in the diabetic rat group fed a diet of C. rasemosa seaweed were still higher than the control group but 15.53% lower than the diabetic group fed standard diet.